Blockchain Technology: Cyber Security Strategy in Post-2007 Cyber-Attacks Estonia - Dita Aulia Salma; Fahlesa Munabari (Deviance Jurnal kriminologi, 2023)
This article analyzes how blockchain technology became one of Estonia's cybersecurity strategies after cyberattacks against Estonia that occurred in 2007. As a result of these attacks, Estonia was able to significantly strengthen its cybersecurity. Using offensive and defensive perspectives, the article analyzes Estonia's steps to deal with cyberattacks in 2007 and the strategies used as anticipatory measures in preventing similar attacks in the future. This article also analyzes the use of blockchain technology in Estonia after the cyber-attacks in 2007. This article argues that the use of blockchain technology has not only strengthened Estonia's cybersecurity, but also been a counterbalance to the power of cybersecurity for Estonia's European neighbors, including Russia.